An assessment of feeding jejunostomy tube placement at the time of resection for gastric adenocarcinoma: A seven‐institution analysis of 837 patients from the U.S. gastric cancer collaborative. Issue 2 (4th August 2015) - Dann, Gregory C.; Squires, Malcolm H.; Postlewait, Lauren M.; Kooby, David A.; Poultsides, George A.; Weber, Sharon M.; Bloomston, Mark; Fields, Ryan C.; Pawlik, Timothy M.; Votanopoulos, Konstantinos I.; Schmidt, Carl R.; Ejaz, Aslam; et al.
<x xml:space="preserve">Abstract</x> Background Jejunostomy feeding tubes (J‐tubes) are often placed during resection for gastric adenocarcinoma (GAC). Their effect on postoperative complications and receipt of adjuvant therapy is unclear. Methods Patients who underwent curative‐intent resection of GAC at seven institutions of the U.S. Gastric Cancer Collaborative from 2000 to 2012 were identified. The associations of J‐tubes with postoperative complications and receipt of adjuvant therapy were determined. Results Of 837 patients, 265 (32%) received a J‐tube. Patients receiving J‐tubes demonstrated greater incidence of preoperative weight loss, lower BMI, greater extent of resection, and more advanced TNM stage. J‐tube placement was associated with increased infectious complications (36% vs. 19%; P < 0.001), including surgical‐site (14% vs. 6%; P < 0.001) and deep intra‐abdominal (11% vs. 4%; P < 0.001) infections. On multivariate analysis, J‐tubes remained independently associated with increased risk of infectious complications (all: HR = 1.93; P = 0.001; surgical‐site: HR = 2.85; P = 0.001; deep intra‐abdominal: HR = 2.13; P = 0.04). J‐tubes were not associated with increased receipt of adjuvant therapy (HR = 0.82; P = 0.34). Subset analyses of patients undergoing total and subtotal gastrectomy similarly demonstrated an association of J‐tubes with increased risk of infectious outcomes and no association with increased receipt of adjuvant therapy. Conclusions J‐tube placement after resection of gastric adenocarcinoma is associated with increased postoperative infectious outcomes and is not associated with increased receipt of adjuvant therapy. Selective use of J‐tubes is recommended. J. Surg. Oncol. 2015 111:195–202. © 2015 Wiley Periodicals, Inc.